New Nanocomposite Derivatives From Thiadiazole Polymers /Silica Synthesis and Characterization using Free Radical Polymerization - Abid, Nasir S.; Sultan, Maha T.; Tomma, Jumbad H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
A new class of thiadiazole /silica nanocomposites with chemical bonds between thiadiazole monomers and modified nanosilica surface were synthesized by free radical polymerization. Presence silica nanoparticles in the structure of  nanocomposite showed effectively improve the physical and chemical properties of Producing polymers. A nanocomposite material with feature properties comparison with their polymers, The structure and morphology of the synthesis materials were investigated by FT-IR spectrum which display preparation new thiadiazole compounds and polymerization monomers. FT-IR showed disappeared double bond (C=C) of monomers, due to produce long chains of thiadiazole polymers and nanocomposite. X-ray diffraction gave idea about crystalline structure of nanoparticles and nanocomposite , X-ray showed that silica nanoparticles have high intensity at 18000 , due to nanoscale of particles which allowed for particles aggregation together. While nanocomposite show low intensity due to reacted thiadaizole polymer chains with silica nanoparticles surface. The distribution of nanoparticles had characterized by Atomic forces microscopy AFM. AFM results shown roughness in the surfaces of nanocomposites C1 and C2, comparison with silica nanoparticles which gave smooth surface. The roughness attributed to reaction between functionalized surface of silica nanoparticles and chains of thiadaizole polymers, which led to change in size particles distribution and surface of particles that refer to nanocomposite.